2011
DOI: 10.1186/1472-6963-11-224
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and medical second trimester abortion in South Africa: A cross-sectional study

Abstract: BackgroundA high percentage of abortions performed in South Africa are in the second trimester. However, little research focuses on women's experiences seeking second trimester abortion or the efficacy and safety of these services.The objectives are to document clinical and acceptability outcomes of second trimester medical and surgical abortion as performed at public hospitals in the Western Cape Province.MethodsWe performed a cross-sectional study of women undergoing abortion at 12.1-20.9 weeks at five hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
4
29
0
1
Order By: Relevance
“…Interviewees reported that this occurs because often women do not know they are pregnant. Explanations for this included the wide use of Depo‐Provera and associated amenorrhea, difficulty in scheduling appointments for abortions, and/or long wait times at facilities …”
Section: Remaining Concernsmentioning
confidence: 99%
“…Interviewees reported that this occurs because often women do not know they are pregnant. Explanations for this included the wide use of Depo‐Provera and associated amenorrhea, difficulty in scheduling appointments for abortions, and/or long wait times at facilities …”
Section: Remaining Concernsmentioning
confidence: 99%
“…The baseline survey was completed in 2008, [9] and the data reported here are derived from a second round of data collection in 2010. Study sites included four public hospitals in the Western Cape that provided second-trimester abortion services, which were selected according to the volume of women seeking abortion services.…”
Section: Methodsmentioning
confidence: 99%
“…Service provision also needs to be strengthened by making services more acceptable and woman-friendly, including reducing the delays experienced by women seeking abortion care at public facilities. [9] …”
Section: Study Limitations and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence further suggests that women who are of lower socioeconomic status (Harries et al 2015; Trueman and Magwentshu 2013), (Black) African (Constant et al 2014), living with HIV (National Committee for the Confidential Enquiries into Maternal Deaths 2014; Orner et al 2011; Stevens 2012) and/or residing in Gauteng, Limpopo or KwaZulu-Natal (National Committee for the Confidential Enquiries into Maternal Deaths 2014) are at higher risk of unsafe abortion and its health consequences than women who are more affluent, White, living without HIV and/or residing in other provinces. South African women have identified a number of barriers to safe abortion care including fear of discrimination or confidentiality breech, abuse and neglect by health workers, a dearth of abortion providers, waiting lists, gestational limits, long distances, insufficient knowledge about abortion laws and financial constraints (Constant et al 2014; Cooper et al 2004; Grossman et al 2011; Harries et al 2007, 2015; Jewkes et al. 2005; Trueman and Magwentshu 2013; Stevens 2012; Vincent 2012).…”
Section: Introductionmentioning
confidence: 99%